A comprehensive review on classifying fast-acting and slow-acting antimalarial agents based on time of action and target organelle of Plasmodium sp. Issue 1 (19th May 2022) - Mariebernard, Monika; Mohanty, Abhinab; Rajendran, Vinoth
Abstract: The clinical resistance towards malarial parasites has rendered many antimalarials ineffective, likely due to a lack of understanding of time of action and stage specificity of all life stages. Therefore, to tackle this problem a more incisive comprehensive analysis of the fast- and slow-acting profile of antimalarial agents relating to parasite time–kill kinetics and the target organelle on the progression of blood-stage parasites was carried out. It is evident from numerous findings that drugs targeting food vacuole, nuclear components, and endoplasmic reticulum mainly exhibit a fast-killing phenotype within 24 h affecting first-cycle activity. Whereas drugs targeting mitochondria, apicoplast, microtubules, parasite invasion, and egress exhibit a largely slow-killing phenotype within 96–120 h, affecting second-cycle activity with few exemptions as moderately fast-killing. It is essential to understand the susceptibility of drugs on rings, trophozoites, schizonts, merozoites, and the appearance of organelle at each stage of the 48-h intraerythrocytic parasite cycle. Therefore, these parameters may facilitate the paradigm for understanding the timing of antimalarials action in deciphering its precise mechanism linked with time. Thus, classifying drugs based on the time of killing may promote designing new combination regimens against varied strains of Plasmodium falciparum and evaluating potential clinical resistance. Abstract : The review highlights classifying fast and slow-acting antimalarial agents relating to parasite killing time and the appearance of organelle at each stage of intraerythrocytic development of P. falciparum .